Academic Senate Minutes 2004-11-11 - Academic Senate:::::::::
Chair Report. Approval of Agenda - item added: Call for an Independent Investigation Into the Actions of CSU Chancellor Castro as President of CSU Fresno, and for an Effective CSU Response to Prevent Future Such Incidents - Approved. Minutes of 2/3/22 - Approved. President Report. Provost Report. Associated Students Report. Proposal for the Senate to be virtual for the AY 22-23 - First Reading completed. From EPC: Early Childhood Studies BA, Education Minor, Discontinuation Early Childhood Education Certificate, Discontinuation Concentration in Early Childhood MA - Second Reading - All Approved. Resolution: Call for an Independent Investigation into the Actions of CSU Chancellor Castro as President of CSU Fresno, and for an Effective CSU Response to Prevent Future Such Incidents - First Reading waived, amended and Approved. Staff Representative Report.